The Role of CSR and Ownership Committees in Industrial Company Strategies in Indonesia - Hery Haryanto; Johanes Prawira (Eduvest - Journal of Universal Studies, 2024)
In business, particularly in Indonesia, the implementation of Corporate Social Responsibility (CSR) concepts has become essential. CSR disclosure is often regarded as a strategy to enhance a company's brand and meet societal expectations, despite ongoing debates about its applicability and efficacy. Nevertheless, Indonesian businesses have yet to fully embrace investments that prioritize sustainable financial principles and ecologically beneficial characteristics. The efficacy of a company's climate change strategy is contingent upon the participation of the CSR committee, and the successful execution of climate change management methods is largely dependent on CSR spending. However, differences exist between the effects of family and managerial ownership on business operations. This study examines the connections between CSR disclosure, the function of CSR committees, CSR spending, managerial and family ownership, and the performance of Indonesian firms. The research's conclusions offer significant insights for businesses in terms of performance enhancement and meeting stakeholder expectations